The Role of GI Peptides in Functional Dyspepsia and Gastroparesis: A Systematic Review - Van den Houte, Karen; Scarpellini, Emidio; Verbeure, Wout; Mori, Hideki; Schol, Jolien; Masuy, Imke; Carbone, Florencia; Tack, Jan (Frontiers in Psychiatry, 2020)
Functional dyspepsia (FD) and gastroparesis (GP) are common disorders of the upper gastrointestinal tract. The pathophysiology of these conditions is likely to be heterogenous, and factors such as altered motility, sensitivity and response to nutrition have been identified as putative underlying mechanisms. Motility, sensitivity as well as responses to nutrition can be influenced or mediated by peptide hormones and serotonin released from the gastrointestinal mucosa. This review summarizes the role of GI peptides in functional dyspepsia and gastroparesis. In most studies, the levels of somatostatin, ghrelin, and motilin did not differ between healthy volunteers and FD or GP patients, but higher symptom burden was often correlated with higher peptide levels. Ghrelin and motilin receptor agonists showed promising results in improvement of the gastric emptying, but the link with improvement of symptoms is less predictable. Serotonin agonists have a potential to improve symptoms in both FD and idiopathic gastroparesis. Drugs acting on the GLP-1 and on the PYY receptors deserve further investigation. There is a need for systematic large scale studies.